The Emperior and the nightingale - Crook, Marie (London : Penguin, 2000)
Despite beingneglected by the emperor for a jewel-studded bird, the little nightngale revives the dying ruler with its beautiful song.
Keywords: Fairy tales; Nightgales -- Fiction